Ali obstaja življenje na eksoplanetu Maja? - Planinšič, Gorazd (Presek, 2014)
Astronomy and astrophysics are very popular with pupils, but the experimental work they can do tends to be rather limited. The search for life elsewhere in the Universe ('exobiology') has received an enormous boost since the detection of a rapidly increasing number of planets ('exoplanets') orbiting other stars in our galaxy. Recently (March 2012), a technique has been devised to determine if an exoplanet might be a suitable host for life. Despite the fact that exoplanets themselves cannot be resolved as separate objects, the technique exploits the polarization properties of the light they reflect from their parent star. This paper describes how this technique can be replicated easily on a model system in the school laboratory.
Keywords: astronomija; planeti; poučevanje